Smart Agriculture Using IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Internet of Things (IOT) is  transforming agricultural by incorporating farmers in a  variety of approaches to tackle challenges in the field,  like as precise and conservatism farming. Harvest web  surveillance includes weeds region, fluid levels, insect  recognition, and mammal disturbance in the field, as well  as change development and culture. IoT stands for  Internet of Things, and it is a rapidly growing technology  in all areas of automation. Actual time weather  observation is the most important for agriculture, since it  may address many agricultural-related problems. Water is  a valuable and essential resource in the globe. As a result,  we must use water only when it is required and avoid  wasting it; this conserves water. In the agricultural sector,  sensors are used to perform smart agriculture. This sensor  helped in the monitoring of the agricultural environment  and the collection of data on the land fields. This system  uses wireless sensor technologies to monitor crops. We  can check real-time data like as water level, soil moisture,  temperature, and moisture using the sensors.
Keywords: Agriculture; IoT; Smart Agriculture; Sensor; Soil